Entre práticas e apropriações: os gêneros retórico-poéticos do Folheto de Ambas Lisboas (1730-1731) - Brito, Suelen Oliveira de (2019)
This research aims to analyze and highlight the rhetorical-poetic genres of the Ambas Lisboa Leaflet (1730 - 1731) as well as investigate the relation between this portuguese leaflet and the unofficial journal Gazeta de Lisboa Occidental (1715-1760). Therefore, it was sought to reestablish the reading and writing practices that governed the genres in the 18th century. In this analysis, it was used procedures foreseen and applied by the lettered conventions in activity time (PÉCORA, 2001) of circulation of the jocular leaflet assigned to Jerônimo Tavares Mascarenhas de Távora and his collaborator Victorino José. To do so, a cataloging and a qualitative analysis of the rhetorical-poetic genres were made, in order to point out the newspaper as an experimental space that give vent to written production in the 18th century. The study is methodologically based on Cultural History, which took a different look at what it commonly has about the literary objects of the past, conceiving them as the fruit of a historical time, providing value to the support and considering relegated, erased and despised authors and objects because of an anachronistic view present in Literary Historiography which condemned them to oblivion and silence. Thus, it was extremely important to observe the prescriptions of the historiography of the time for these genres, the speech place of the writers, the importance of supporting the spreading and circulation of rhetorical-poetic genres, and also the rhetorical and poetic prescriptions of the writings at that time. For this purpose, it was considered the studies of Barbosa (2007; 2017), Carvalho (2007), Chartier (1990; 1991; 1999; 2004), Gamma (1846; 1851), Hansen (2013), Honorato (1879), Lopes Moraes (1856), Machado (1746), Mattoso (2011), Mckenzie (2004), Mello Moraes (1856), Moraes Silva (1789) Mota (2003; 2005) and Pécora (2001), Quintiliano (2015) among others. In addition, it was resorted to the electronic archives of the Ambas Lisboa Leaflet and the Gazeta de Lisboa Occidental (1715-1760) from the National Library of Portugal recognizing the primary sources as important research sources.